UV-curable hyperbranched polyester sealant with tunable mechanical properties. (October 2021) - Jiao, Yan; Chu, Lili; Zhu, Miaomiao; Wei, Yingqi; Wang, Weicai; Wang, Huaiming; Wang, Hui
Different types of wounds have different requirements of a wound sealant. One of the requirements of concern is the adaptability of the mechanical properties of biomaterials to native tissues. However, the mechanical properties of current sealant are untunable or adjustable in a small range normally. Therefore, the scope of application of these sealant is limited. In this study, we developed hyperbranched polyester (HBP)-based UV-curable sealant with tunable mechanical properties. This sealant was cured under UV-light for 2 minutes and exhibited strong adhesion with tissues. The shear adhesive strength of it to the porcine skin ranged between 20–30 kPa, which was higher than the fibrin glue (∼10 kPa). Moreover, the elastic modulus of the sealant in a tensile test ranged between 27–54 MPa, depending on the degree of acrylation of the HBPs. Additionally, we assessed the biocompatibility of the sealant by co-culturing it with mouse mesenchymal stem cells (mMSCs) for 7 days and discovered that the cell viability was unaffected. This sealant with a tunable elastic modulus might be a promising candidate for treating wounds with different elastic moduli.